Microelectronics, Electromagnetics and Telecommunications Proceedings of ICMEET 2017 - Anguera, Jaume; Satapathy, Suresh Chandra; Bhateja, Vikrant; Sunitha, K.V.N.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
The volume contains 94 best selected research papers presented at the Third International Conference on Micro Electronics, Electromagnetics and Telecommunications (ICMEET 2017) The conference was held during 09-10, September, 2017 at Department of Electronics and Communication Engineering, BVRIT Hyderabad College of Engineering for Women, Hyderabad, Telangana, India. The volume includes original and application based research papers on microelectronics, electromagnetics, telecommunications, wireless communications, signal/speech/video processing and embedded systems.
Preface -- Organising Committee -- Table of Contents -- 94 papers -- Author Index.
Keywords: Electronics; Electronic circuits; Telecommunication; Electronics and Microelectronics, Instrumentation; Electronic Circuits and Systems; Communications Engineering, Networks